(untitled) (Journal of Fiber Bioengineering and Informatics, 2008)
In this paper, the theoretical heat transfer of flexible thermal insulation composite fabric has been analyzed and the designing method has been discussed in systematically. Heat transfer analysis of flexible thermal insulation composite fabric is sometimes too complex to be used in practical design application. So, it is necessary to have simpler methods to evaluate the heat transfer flux through multilayer thermal insulation. The paper presented experimental and theoretical studies on the determination of the effective thermal conductivities of the flexible thermal insulation composite fabric. A mathematical model has been developed to describe the heat flux through the composite fabric, where the heat transfer consists of thermal radiation, solid spacer and residual gas conduction. The three distinct heat transfer modes are treated as parallel thermal resistances, and the multilayer thermal insulation behaviour considering a layer-to-layer approach and is based on an electrical analogy. Then, thermal performances of flexible thermal insulation composite fabric are presented, selecting different materials, different layers and different spacers. Finally, the prime structure of the flexible thermal insulation composite fabric is obtained through the theoretical and experimental analysis.